Asperteramide A, an Unusual N‐Phenyl‐Carbamic Acid Methyl Ester Trimer Isolated from the Coral‐Derived Fungus Aspergillus Terreus. Issue 18 (30th April 2019) - Liu, Mengting; He, Yan; Shen, Ling; Anbari, Weaam Hasan Al; Li, Huaqiang; Wang, Jianping; Qi, Changxing; Hu, Zhengxi; Zhang, Yonghui
Abstract : Asperteramide A, an unusual N ‐phenyl‐carbamic acid methyl ester trimer, was isolated and identified from the coral‐derived fungus Aspergillus terreus . The deceptive and indistinguishable NMR signals caused by three N ‐phenyl‐carbamic acid methyl ester subunits located in different spatial environments created great challenge for the identification of its planar structure, but recrystallization ultimately afforded a suitable crystal for the X‐ray diffraction experiment, which enabled its final structure determination. The plausible biosynthetic pathway of1 mainly involved in the successive Friedel–Crafts reactions. Additionally, compound1 showed significant antibacterial activity against seven microbial pathogens [ESBL‐producing Escherichia coli, Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, methicillin‐resistant Staphylococcus aureus, Enterococcus faecalis, Candida albicans ] with MIC values ranging from 2 to 64 µg/mL. Abstract : Chemical investigation of the coral‐derived fungus Aspergillus terreus resulted in the identification of asperteramide A, an unusual N ‐phenyl‐carbamic acid methyl ester trimer. Compound1 showed potential antibacterial activity.